Hecho en Tejas Texas-Mexican Folk Arts and Crafts - Graham, Joe S.; Project Muse. (Texas A & M University Press [distributor], 1997)
Annotation When the early Spanish and Mexican colonists came to settle Texas, they brought with them a rich culture which enabled them to settle and build a civilization in a wild land. The broad intracultural diversity of these settlers from different parts of Mexico and Spain are nowhere more evident in Texas than in the material culture--folk art, folk craft, architecture--which is part of our Spanish-Mexican legacy in Texas. Hecho en Tejas, the first book-length publication to focus on Texas-Mexican material culture, shows the richness of Tejano folk arts and crafts traditions through essays on Hispanic folk art in San Antonio in the home and yard, and on the street; through quilting traditions; through the vaqueros' traditions of weaving horsehair ropes and plaiting rawhide for quirts and bridles, and making of saddles; making of paper flowers as coronas para los muertos--primarily for decorating graves; making of ceramic figures for religious and secular use; the making of stringed instruments; the making of pinatas; religious folk art and yard art, grutas, roadside crosses, as well as religious matachines dance traditions; jacales as a form of folk house, and the built-environment of a Texas-Mexican ranch. A bibliography of Texas Mexican Material Culture is included.
Description based on print version record.
Keywords: Mexican American folk art; Mexican American folk art -- Texas; Texas; Electronic books